2011
DOI: 10.1074/jbc.m110.217802
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Helix 1 Contributes to Substrate Translocation and Protein Stability of Bile Acid Transporter SLC10A2

Abstract: The human apical sodium-dependent bile acid transporter (hASBT, SLC10A2) plays a critical role in the enterohepatic circulation of bile acids, as well as in cholesterol homeostasis. ASBT reclaims bile acids from the distal ileum via active sodium co-transport, in a multistep process, orchestrated by key residues in exofacial loop regions, as well as in membrane-spanning helices. Here, we unravel the functional contribution of highly conserved transmembrane helix 1 (TM1) on the hASBT transport cycle. Consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Western blotting was also preformed as previously described. 17 Briefly, samples were loaded onto precast, 15 well, 12% Tris-HCl Polyacrylamide gel (BioRad 456–1046) along with 2.5 μL Li-cor Odyssey two-color protein molecular weight marker (928-40001). A custom antibody (1:1,000) was used to visualize the glycosylated (41 kDa) and unglycoslyated (38 kDa) hASBT protein.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was also preformed as previously described. 17 Briefly, samples were loaded onto precast, 15 well, 12% Tris-HCl Polyacrylamide gel (BioRad 456–1046) along with 2.5 μL Li-cor Odyssey two-color protein molecular weight marker (928-40001). A custom antibody (1:1,000) was used to visualize the glycosylated (41 kDa) and unglycoslyated (38 kDa) hASBT protein.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was followed as described previously [25]. Briefly, cells were washed with icecold DPBS twice and then incubated with EZ Link NHS-SS-biotin (1 mg/ml) for 30 min at 4 • C. The reaction was quenched with 1 M Tris/HCl (pH 7.4).…”
Section: Western Blotting and Surface Biotinylationmentioning
confidence: 99%
“…Medium was changed on alternate days after confluency. The uptake studies were carried out as described previously [25]. Briefly, cells were washed twice with DPBS (Dulbecco's PBS) and then incubated at 37 • C for 12 min (previous studies have shown that TCA uptake is linear up to 15 min and 10 min in COS-1 and Caco-2 cells respectively) [23,26] …”
Section: Introductionmentioning
confidence: 99%
“…TCA Uptake Study-Uptake studies were carried out as previously described (11). Briefly, COS-1 cells were transiently transfected with pCMV5 plasmid containing C270A mutant, TM2 mutants, or WT_ASBT DNA.…”
Section: Materials-radiolabeledmentioning
confidence: 99%
“…For example, mutations on ϳ70% TM1 residues resulted in impaired function (11), with residue Leu 30 critical for both bile acid and sodium binding. The large hydrophilic region lining the cytosolic half of TM3 may be partially involved in substrate exit during bile acid translocation (12).…”
mentioning
confidence: 99%